45.4k views
12 votes
What is the solution to the equation −4(2y − 4) − 4y = 4? (put number answer only)

2 Answers

4 votes

Answer:

y=1

Explanation:

Let's solve your equation step by step.

Step 1: Simplify both sides of the equation.

−4(2y−4)−4y=4

(−4)(2y)+(−4)(−4)+−4y=4(Distribute)

−8y+16+−4y=4

(−8y+−4y)+(16)=4(Combine Like Terms)

−12y+16=4

−12y+16=4

Step 2: Subtract 16 from both sides.

−12y+16−16=4−16

−12y=−12

Step 3: Divide both sides by -12.

y=1

User Alexey Chuhrov
by
5.9k points
6 votes
-8y + 16 - 4y = 4
-12y + 16 = 4
-12y = -16
Y = 1.3333333
User Yzmir Ramirez
by
6.0k points